Autoinducer-2 Quorum Sensing Influences Viability of Escherichia coli O157:H7 under Osmotic and In Vitro Gastrointestinal Stress Conditions - Park, Hyunjoon; Lee, Kyuyeon; Yeo, Soyoung; Shin, Heuynkil; Holzapfel, Wilhelm H. (Frontiers in Microbiology, 2017)
Bacteria use autoinducer molecules to communicate both at intra-species and inter-species levels by quorum sensing. One such cell density-dependent signaling system is the luxS-mediated universal quorum sensing using autoinducer-2 (AI-2). Virulence of several pathogens is determined by an AI-2 system and is related to colonization and infection of the host. From this concept, numerous papers have suggested that AI-2 inhibition is an important strategy toward designing of new antimicrobial agents. However, recent studies indicate that the AI-2 system is also involved in adaptation and survival under environmental stress conditions. Therefore, we hypothesized that interaction between quorum sensing and environmental conditions may be critical in influencing predicted results in a control and when combating of target pathogens. We investigated the growth of enterohemorrhagic Escherichia coli O157:H7 (EHEC) and its luxS-deficient (non AI-2 producing) mutant strain under various stress conditions, and found significant differences in the growth rate under osmotic stress. Moreover, we could also show the impact of the AI-2 molecule on viability in the gastrointestinal tract model representing a complex environmental condition. Differences in vital responses of the strains suggest that AI-2 quorum sensing has a significant influence on the viability of EHEC under environmental stress conditions.